PTH-201 Factors affecting the efficacy of needlefree connector disinfection. (22nd June 2015) - Small, M; Robinson, D; Patel, S
Abstract : Introduction: Needlefree connector contamination can lead to central venous catheter related bloodstream infection (CRBSI). Differences in connector design such as a smooth or irregular septum surface and/or a tight seal between the septum and the connector housing can impede disinfection. Disparity between protocols; disinfectant contact time, disinfection method (if the surface is wiped in one direction or back and forth) and inter rater variation may also affect results. This invitro study aimed to assess these variables on the macroscopic contamination of different connectors. Method: The surfaces of 5 different needlefree connectors were contaminated with ultraviolet (UV) disclosing lotion (invisible to the naked eye). 3 raters subsequently wiped the connectors with 2% chlorhexidine and 70% isopropyl alcohol wipes using a friction rub for 0 (control) 3, 5, 15 and 30 secs. Using UV light the amount of residual lotion on the connectors was assessed and scored accordingly; 100 if there was no trace of lotion, 75 a minimal trace, 50 a moderate trace and 25 if a large trace remained. These values were decided by 2 raters. The procedure was then repeated following the application of 70% isopropyl alcohol port protection caps to the connector for 5 min before disinfection. Results: The mean score ±standard deviation from all connectors and all raters is shown below. Variation between devices was significant p < 0.0001. Higher scores were obtained when port protection was applied pre disinfection vs. no port protection. The difference between these was significant p < 0.0001. The mean score for disinfecting <10secs was 69 ± 23.4 vs. 83 ± 17.7 for >10 secs. This difference was significant p < 0.0001. There was a difference between 3 and 5 secs; 65 ± 24 vs. 74 ± 22, p = 0.03, but no difference between 15 vs. 30 secs; 82 ± 17.9 vs. 83 ± 17.7, p = 0.6. The scores from the 3 raters were 78 ± 21 vs. 78 ± 19.9 vs. 70 ± 23 respectively. Variation between raters was significant p = 0.01. There was no difference between raters when the port protector was applied pre disinfection p = 0.19. Conclusion: The results from this study demonstrated differences in the removal of macroscopic contamination from needlefree connectors. These differences most likely reflect variation in the surface topography of the individual connectors. Disinfecting for 10 secs or more was more effective than less than 10 secs, with 15 secs being as effective as 30 suggesting a minimum of 15 secs is sufficient. There was variation between raters but this was minimised by using a 70% isopropyl alcohol port protector. The extent to which these results could impact upon the development of CRBSI will be the focus of future study. Disclosure of interest: None Declared.